Occurrence of Partial Albinism in Lesser Mouse-Tailed Bat Rhinopoma hardwickii in Kachchh District of Gujarat, India - Senacha, K. R.; Joshi, Arpan; Dookia, Sumit; Rawat, Mamta; Bohra, Mayank (Journal of the Bombay Natural History Society (JBNHS), 2025)
No Abstract.